1998
DOI: 10.1007/s11738-998-0010-8
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis, respiration, and chlorophylls in presenescent, regreened, and senescent leaves of forest herb Smyrnium perfoliatum L. (Apiaceae)

Abstract: Smyrnium perfoliatum L. (Apiaceae), an endangered forest herb with only one main locality in South-West Slovakia (Devfnska Kobyla in the Little Carpathian Mountains), is capable to recover chlorophylls at the end of the growing season. This regreening only within bracts was observed dturing two weeks before achieving the so-called "point of no return" that leads to the last stage of ontogenesis -leaf senescence. The effect not only of endogenous cytokinins on chlorophyll content and carbon dioxide exchange (ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It has been suggested that there is a 'point of no return' separating the pre-senescence from the irreversible senescence phase and that this point is associated with the disappearance of plastid ribosomes. However, the regulation and biochemical basis of the switch to irreversible senescence is not known (Ness and Woolhouse, 1980;Olah and Masarovicova, 1998;reviewed in van Doorn, 2005;Zubko and Day, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that there is a 'point of no return' separating the pre-senescence from the irreversible senescence phase and that this point is associated with the disappearance of plastid ribosomes. However, the regulation and biochemical basis of the switch to irreversible senescence is not known (Ness and Woolhouse, 1980;Olah and Masarovicova, 1998;reviewed in van Doorn, 2005;Zubko and Day, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that conversion of chloroplasts to gerontoplasts, and therefore leaf senescence, may be reversible in several species if the senescing tissue is exposed to conditions favoring re-greening (e.g., exogenous application of cytokinins). However, this reversal is only possible before the terminal phase has been initiated and if the "point of no return" is not surpassed (Karagiannis and Pappelis, 1994;Bhattacharya et al, 1996;Olah and Masarovicova, 1998;Zavaleta-Mancera et al, 1999a, b). The 'point of no return' is that point at which, once passed, the leaf is committed to death.…”
Section: Some Fundamental Questions Andmentioning
confidence: 99%
“…On the other hand, the chlorophyll content can be stimulated by endogenous cytokines, irradiance, temperature and drought stress (Olah, Masarovikova 1998;Afreen 2005).…”
Section: Effect Of Elf-emf On the Chlorophyll Content Of Tissue-cultumentioning
confidence: 99%